2021
DOI: 10.1071/an20396
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, feeding and laying hen welfare

Abstract: The relationship between nutrition and welfare is usually considered to be a direct result of supplying the hen with adequate quantities of feed and water. This simple notion of freedom from hunger and thirst belies the fact that nutrients play a pivotal role in the body’s response to challenges whether they relate to ambient temperature, gastrointestinal health, pathogen exposure, metabolic disorders, or social and mental stress. In all instances, maintaining homeostasis and allowing for physiologic response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 200 publications
0
16
0
11
Order By: Relevance
“…In particular, on the diet of the hens in different types of creation, compared to the feed commonly used in conventional cage creation, organic farming (and in cagefree farming) favors the predominant consumption of grass from external areas, which provides high amounts of fiber, tocopherol, carotenoids and flavonoids (20), allowing a remarkable transfer of bioactive substances that could confer higher nutritional quality to the organic egg compared to the conventional egg. In addition, it has also been shown that cage-free housing and the guarantee of adequate outdoor space for the animal behavior of all livestock ensures that laying hens can move freely during some hours of the day and, consequently, are less stressed (37). It is understandable that the result of this set of measures based on sustainability, high-quality animal nutrition, and animal welfare results in a feed that generates a lower environmental footprint (38,39) and, above all, a higher nutritional density (6) compared to conventional egg production.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, on the diet of the hens in different types of creation, compared to the feed commonly used in conventional cage creation, organic farming (and in cagefree farming) favors the predominant consumption of grass from external areas, which provides high amounts of fiber, tocopherol, carotenoids and flavonoids (20), allowing a remarkable transfer of bioactive substances that could confer higher nutritional quality to the organic egg compared to the conventional egg. In addition, it has also been shown that cage-free housing and the guarantee of adequate outdoor space for the animal behavior of all livestock ensures that laying hens can move freely during some hours of the day and, consequently, are less stressed (37). It is understandable that the result of this set of measures based on sustainability, high-quality animal nutrition, and animal welfare results in a feed that generates a lower environmental footprint (38,39) and, above all, a higher nutritional density (6) compared to conventional egg production.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, eggs of hen breeds with the highest mineral content might highly influence the physiological functions of bones and teeth (Ca), transportation of oxygen (Fe), immunity maintenance (lutein and zeaxanthin nutrients), metabolic activities, DNA construction, and maintenance (Zn) of consumers from that egg breeds [47] [48]. Presumably, the difference in ash content might be attributed to the variation in the genetic sensitivity response of breeds that drank saline drinking water [49]. A significantly (P ≤ 0.01) highest egg crude fiber content was confirmed for KK (1.63 ± 0.11), higher for CH (1.44 ± 0.07) breeds, whereas the lowest egg crude fiber content was observed for HC (1.36 ± 0.05), C (1.33 ± 0.05), L (1.29 ± 0.01) and H (1.25 ± 0.05) breed eggs.…”
Section: Nutritional Composition Of Eggs Of Different Chicken Genotypesmentioning
confidence: 99%
“…The crude ash content from breeds had a positive significant correlation with crude fiber (r = 0.970; P < 0.01. The direct association of crude ash content and fat accumulation might be attributed to the physiological response of eggs from breeds drunk saline drinking water [49].…”
Section: External and Internal Egg Qualitymentioning
confidence: 99%
“…Together, this is a very strong endorsement for the role of probiotics in promoting gut health, and animal health and productivity. Moreover, probiotic use will also have a positive impact on animal and bird welfare (Bryden et al 2021). Importantly, there is increasing evidence that the gut microbiota plays a central role not only in physical, but also mental wellbeing, with obvious implications for bird health and welfare (Kraimi et al 2019).…”
Section: Box 1 Necrotic Enteritismentioning
confidence: 99%